2009
DOI: 10.1007/s00774-009-0040-3
|View full text |Cite
|
Sign up to set email alerts
|

Osteoinductive capacity and heat stability of recombinant human bone morphogenetic protein-2 produced by Escherichia coli and dimerized by biochemical processing

Abstract: One problem associated with clinical application of CHO-derived recombinant human bone morphogenetic protein (C-BMP-2) is its high cost due to the need for use of high doses. To solve this problem, Escherichia coli-derived BMP-2 (E-BMP-2) has been examined using the technique of molecular unfolding and refolding. However, it is unclear whether the characteristics of E-BMP-2 are appropriate for clinical application. In this study, we examined the biological activity of E-BMP-2 and its heat tolerance in in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…In contrast to CHO-BMP-2, E-BMP-2 is not glycosylated, but previous in vitro studies suggested that its biological activity is similar to that of CHO-BMP-2 [22,23]. Thus, the bacterial expression system appears to offer a viable method for achieving an extremely high protein output at a relatively low cost [21].…”
Section: Introductionmentioning
confidence: 63%
“…In contrast to CHO-BMP-2, E-BMP-2 is not glycosylated, but previous in vitro studies suggested that its biological activity is similar to that of CHO-BMP-2 [22,23]. Thus, the bacterial expression system appears to offer a viable method for achieving an extremely high protein output at a relatively low cost [21].…”
Section: Introductionmentioning
confidence: 63%
“…Third, our sample size in each group was not sufficient to yield substantial effects and the study is likely underpowered; we therefore consider the study preliminary. On the other hand, we previously found E-BMP-2 has osteoinductive activity equivalent to that currently produced in BMP-2 gene-transfected animal cells (Chinese hamster ovary cells) [45]. However, it is essential to evaluate the safety of E-BMP-2 for clinical use.…”
Section: Discussionmentioning
confidence: 95%
“…However, it is essential to evaluate the safety of E-BMP-2 for clinical use. In several previous studies using E-BMP-2 [18,29,45], its safety was not sufficiently examined. Evaluation of the safety of E-BMP-2 is required in preclinical studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Initially, BMPs were isolated directly from bones but the yields were low and the process was labourious (Bessho et al 1989;Hu et al 2004). Recombinant human BMPs (rhBMPs) were produced from Escherichia coli (Hillger et al 2005;Yano et al 2009) and mammalian cell culture systems (Israel et al 1992;Wang et al 1990;Yamaguchi et al 1991). Despite successfully producing properly folded, glycosylated and biologically active rhBMP-2, the yield of mammalian cell expression system is low, that remains a major challenge and hinders the use of rhBMP-2 in therapeutic applications.…”
Section: Introductionmentioning
confidence: 98%